Mechanical Thrombectomy Beyond 2b Reperfusion: Should We Pursue a Higher Reperfusion Grade after Achievement of 2b? - Junpei Koge; Kanta Tanaka; Takeshi Yoshimoto; Masayuki Shiozawa; Tsuyoshi Ohta; Tetsu Satow; Hiroharu Kataoka; Masafumi Ihara; Masatoshi Koga; Kazunori Toyoda (Stroke: Vascular and Interventional Neurology, 2022)
Background Extended thrombolysis in cerebral infarction (eTICI) 2c/3 reperfusion after mechanical thrombectomy (MT) is associated with better stroke outcomes than eTICI 2b. Whether additional MT attempt after achieving eTICI 2b (beyond 2b attempt) leads to better outcomes is unknown. Methods Consecutive patients with acute anterior circulation stroke who achieved eTICI 2b during MT were divided into 2 groups: those who further tried MT (beyond‐2b group) and those without (nonbeyond‐2b group). The patients who directly achieved eTICI 2c/3 without experiencing 2b (direct‐2c/3 group) were also studied. The outcomes included the reperfusion status, favorable outcome (3‐month modified Rankin scale score of 0–2), neurological improvement (a ≥10‐point decrease of the National Institutes of Health Stroke Scale score from baseline or the score of 0) at 24 hours and symptomatic intracranial hemorrhage. Results Of 308 patients, 50 were in the beyond‐2b group, 87 in the nonbeyond‐2b group, and the remaining 171 in the direct‐2c/3 group. Perfusion of middle cerebral artery branches supplying the primary motor cortex was worse in the beyond‐2b than the nonbeyond‐2b group at the time of eTICI 2b (P=0.007). Favorable outcome was similarly common (48% for each, P=0.40). Neurological improvement was more frequent (52% versus 37%; P=0.04) and symptomatic intracranial hemorrhage tended to be more common (6% versus 1%, P=0.11) in the beyond‐2b than the nonbeyond‐2b group. Eighteen patients (36%) in the beyond‐2b group finally achieved eTICI 2c/3; 10 of these (56%) and 14 of the remaining 32 (44%) had favorable outcome (P=0.83). The former rate was similar to that in the direct‐2c/3 group (58%; P=0.99). Conclusions Patients undergoing additional MT attempt after achieving eTICI 2b had numerically but not significantly more symptomatic intracranial hemorrhage and showed a similar level of functional outcome at 3 months than those who did not. When eTICI 2c/3 was finally achieved by additional attempts, functional outcome was similar with that of patients who directly achieved eTICI 2c/3 without experiencing 2b. Clinical Trial Registration Information URL: https://www.clinicaltrials.gov. Unique identifier: NCT02251665.